Sustainable Bi-directional thermoregulation fabric for clothing microclimate - Yanyan Lin; Chengran Qu; Xueqin Li; Chengfeng Ding; Xianfeng Wang; Jianyong Yu; Bin Ding (Nature Communications)
Abstract Maintaining the balance of clothing microclimate is critical for human health management. An ideal smart textile should possess key characteristics such as active thermoregulation, moisture permeability, and stable working performance. However, such a fabric that encompasses all these capabilities is rarely reported. Herein, we report a sustainable and durable bi-directional thermoregulation fabric (Bi-DTF) by hierarchical structural engineering strategy. This advancement stems from the programmability of the molecular chains, aiming to reduce chain aggregation, improve functional particle compatibility, and build dynamic stress-dissipative networks, thus fully enhancing the robustness of composite fibrous membranes. The optimized Bi-DTF substantially eliminates the heat/cold irritation caused by environmental switching, featuring high energy storage density (4.1 kJ m−2) and stable work performance even after 50 standard washing cycles and 500 rubbing cycles. Compared with commercial textiles, Bi-DTF offers a maximum thermal temperature difference of only 2.3 °C and a cooling temperature difference of 2.6 °C when going through the heating and cooling cycles. Due to its exceptional personal thermoregulation performance and long-term stability, this proposed strategy exhibits considerable potential for the application of healthcare, outdoor sports, and protective clothing.